Exploring hierarchy situation of 4A marketing mix on Malaysia's fast food restaurants - Nezakati, Hossein; Abu, Mimi Liana; Toh, Cowan (IDOSI Publications, 2011)
Fast Food Restaurant becomes one of the sectors that contribute a lot to the gross domestic product to Malaysia in recent years. In order to penetrate the market of fast food industry in multi racial country, marketers must always take care of food consumption behavior of every ethnic. This study tried to find out the hierarchy situation of 4A marketing mix factors (Affordability, Accessibility, Awareness and Acceptability) in customer perspective instead of marketer perspective that had grown importance in the market. Descriptive analysis and ANOVA analysis were conducted to run as to generate results. Research findings showed that, accessibility situated at the top of the hierarchy, acceptability, awareness and affordability ranked respectively. Therefore, it is crucial for the fast food restaurants and marketing policy makers to take into account these four factors hierarchy to enrich any correspondent marketing strategy.